PENGARUH TERPAAN PEMBERITAAN KASUS FERDY SAMBO DI MEDIA ONLINE TERHADAP TINGKAT KEPERCAYAAN MAHASISWA PADA LEMBAGA KEPOLISIAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The purpose of this study was to determine the level of exposure to news coverage of the Ferdy Sambo case in online media for students of the Faculty of Dakwah and Communication, the level of student trust in the police after experiencing exposure to the news on the Ferdy Sambo case, and the influence of exposure to the news on the Ferdy Sambo case on the level of student trust in the police institution. This study uses a quantitative approach to the survey method. The sample in this study were all active students of the Faculty of Da'wah and Communication at UIN Alauddin Makassar, namely 100 respondents based on the results of calculations using the Slovins formula through the random sampling method. The data collection technique used is a questionnaire. The instrumentation test used is the validity test and reliability test. The data analysis technique used is the classical assumption test (normality test and multicollinearity test), simple linear regression analysis, and hypothesis testing (t-test). The results showed no significant effect on exposure to the news about the Ferdy Sambo case in online media on the level of student trust in the police. The magnitude of the effect as the R2 value obtained was -0.021, in other words -2.1% exposure to the Ferdy Sambo case as an influence on the level of student trust in the police institution. Then based on the results of the hypothesis test (t-test), it is known that the t-count is -0.206, where this value is smaller than the t-table value of 1.98447 at a significance level of 0.05 so Ha is rejected and H0 is accepted. The results of this study, do not support the syringe theory because it does not prove that the mass media has a fast, direct, and consequential impact in stimulating audiences.